2004
DOI: 10.1007/s00436-003-1004-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of exogenous genes in Trypanosoma cruzi : improving vectors and electroporation protocols

Abstract: To improve transfection efficiency in Trypanosoma cruzi, we developed a new electroporation protocol and expression vectors which use luciferase and green and red fluorescent proteins as reporter genes. In transient transfections, the electroporation conditions reported here resulted in luciferase expression 100 times higher than the levels obtained with previously described protocols. To verify whether sequences containing different trans-splicing signals influence reporter gene expression, we compared DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 26 publications
2
104
0
4
Order By: Relevance
“…We engineered the CL-14 to express NY-ESO-1, a well-defined and highly immunogenic CTA, which is currently being tested as a vaccine candidate against cancer in different clinical trials (16)(17)(18)(19). For homologous recombination, we used the pROCKNeo plasmid (20) that promotes insertion of the transgene in one of the many copies of the β-tubulin gene in the T. cruzi genome (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We engineered the CL-14 to express NY-ESO-1, a well-defined and highly immunogenic CTA, which is currently being tested as a vaccine candidate against cancer in different clinical trials (16)(17)(18)(19). For homologous recombination, we used the pROCKNeo plasmid (20) that promotes insertion of the transgene in one of the many copies of the β-tubulin gene in the T. cruzi genome (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic parasites were obtained by cloning the NY-ESO-1 Open reading frame (ORF), fused to His tag or to the gp63 SP sequences into the pROCKNeo plasmid. T. cruzi epimastigotes were transfected and maintained as previously described (20). The integration of the exogenous gene into the parasite genome was confirmed by Southern blot analysis of genomic DNA digested with BamHI and SacI and hybridized with NY-ESO-1 and amastin probes labeled with …”
Section: Methodsmentioning
confidence: 99%
“…However, our previous attempts to knockout TcPI-PLC gene were unsuccessful, and we concluded that the enzyme is essential for T. cruzi (18). In addition, T. cruzi lacks the machinery for RNA interference, which is present in T. brucei (4). To further complicate things, no comparable experiments could be done using T. brucei conditional knockout parasites because, although this parasite possesses an orthologue of TcPI-PLC, it lacks an intracellular stage.…”
Section: Discussionmentioning
confidence: 95%
“…Cells were grown at 288C in liver infusion tryptose (LIT) medium supplemented with 10% fetal calf serum (FCS), as described by Camargo [1964]. Empty pROCKNeo [DaRocha et al, 2004] transfected population were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Fragments obtained after digestion with Spe I and EcoR I were purified and inserted into the Xba I and EcoR I sites of pTREXGFP vector [Vazquez and Levin, 1999] to produce the plasmid pTREXGFP_Polh. Parasites were transfected with pTREXGFP_Polh as described by DaRocha [DaRocha et al, 2004]. Twenty-four hours after electroporation, 5 3 10 6 transfected parasite cells were harvested, washed twice in PBS, and centrifuged at 3,000g for 10 min.…”
Section: Tcpolg Cellular Localization and Confocal Microscopymentioning
confidence: 99%